1999
DOI: 10.4269/ajtmh.1999.61.780
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of mefloquine resistance and amplification of pfmdr1 in multidrug-resistant Plasmodium falciparum isolates from Thailand.

Abstract: Abstract. Resistance to quinoline-containing compound has been associated with the Plasmodium falciparum multidrug resistance 1 (pfmdr1) gene. We analyzed wild P. falciparum isolates with high levels of chloroquine and mefloquine resistance for their macrorestriction maps of chromosome 5 and sequence of pfmdr1. Two types of chromosome 5 amplification were found. Eleven of 62 resistant isolates displayed Bgl I fragments larger than 100 kb. Twenty-nine isolates possessed multiple copies of the fragments. We fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
29
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 24 publications
5
29
0
Order By: Relevance
“…The lack of a polymorphism at position 1246 in this study supported previous reports from Asia, suggesting that this polymorphism may not be important for isolates from this region (4,13,17). Also, the coexistence of elevations in mefloquine, artemisinin, and artesunate IC 50 s for the same categories of isolates is also consistent with previous observations (1,7,16,21).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The lack of a polymorphism at position 1246 in this study supported previous reports from Asia, suggesting that this polymorphism may not be important for isolates from this region (4,13,17). Also, the coexistence of elevations in mefloquine, artemisinin, and artesunate IC 50 s for the same categories of isolates is also consistent with previous observations (1,7,16,21).…”
Section: Discussionsupporting
confidence: 82%
“…Also, some field studies have suggested that mutations or amplification of this gene is associated with chloroquine resistance, while others have suggested that mutations or gene amplification is associated with increased chloroquine sensitivity (1,6). On the other hand, there is more general agreement that mutations in pfmdr1 are associated with altered sensitivity to mefloquine and artemisinin derivatives in vitro, although the role of gene amplification is not clear (1,4,13,14). However, most previous studies were small (n Ļ½ 20 isolates) or limited to single geographical areas where specific polymorphisms may have been absent.…”
mentioning
confidence: 97%
“…[11][12][13] Furthermore, the role of the pfmdr1 gene as a possible factor for the development of multidrug resistance, especially to mefloquine and artemisinin, has recently been proposed. 14,15 The findings from this study indicate a clinically relevant (in vivo) cross-sensitivity between artemisinin and mefloquine, similar to the one previously found in vitro. Such a relationship could have a significant impact on the future development of the artemisinin drug sensitivity of P. falciparum, especially if mefloquine is employed in highly malaria-endemic areas.…”
Section: Discussionsupporting
confidence: 69%
“…However, in other studies no amplification was found in parasites selected for increased resistance (27,40,42). An association between amplification of pfmdr1 and mefloquine resistance has been claimed in some field investigations (34,35,51) but not in others (3,9).…”
mentioning
confidence: 99%